Qualitative analysis of the hypnolearning model in mandarin subjects through smartphones - Darwin, David; Boeriswati, Endry; Setiadi, Samsi (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the implementation of the hypnolearning model in learning Mandarin through smartphone-based applications at Darma Persada University. Using a qualitative approach, data were collected through semi-structured interviews, direct observation, and document analysis. Data analysis was conducted using NVivo 12 software to identify key themes and patterns. The findings indicate that the hypnolearning method effectively enhances students' concentration, memory retention, and understanding of Mandarin characters and tonal pronunciation. Smartphones provide accessibility, flexibility, and interactivity, facilitating learning outside the classroom. Major challenges, such as difficulties in memorizing characters and learning anxiety, are addressed through application features such as relaxation techniques, positive suggestions, and interactive exercises. This study also emphasizes the need for developing application features, training for educators, and collaboration between educational institutions and technology developers to expand access to this method. Recommendations include incorporating gamification, personalized learning, and artificial intelligence (AI) integration to improve the application's effectiveness. The study offers new insights into integrating hypnolearning methods and digital technology, highlighting the potential for innovation in language learning. These findings are particularly relevant for improving the learning experience of complex languages such as Mandarin.